Spolno vedenje slovenskih srednješolcev v letu 2004 - Pinter, Bojana (Zdravniški vestnik, 2006)
Background In order the aim to evaluate the risk-taking behaviour, a representative study on sexual behaviour of secondary-school students in Slovenia was performed. Methods In the spring of 2004, 2380 1st and 3rd grade students from 48 randomly selected secondary schools in Slovenia anonymously completed a self-administered questionnaire. Descriptive statistics was used for data analysis. Results The average students' age was 15.4 years (1st grade) and 17.4 years (3rd grade). Sexual intercourse had ever had 24% of boysand 21% of girls from the 1st grade, and 52% of boys and 54% of girls fromthe 3rd grade. At first sexual intercourse condom was used by 74% of sexually active 1st grade and by 75% of 3rd grade students; 6% of 1st grade and 7% of 3rd grade students used contraceptive pill. At last sexual intercourse condom was used by 65% of sexually active 1st grade and by 50% of 3rd grade students; 11% of 1st grade and 32% of 3rd grade students used the pill. Contraceptive methods and sexually transmitted infections are not sufficiently known to the students. Most students (34%) prefer professionals to be the source of information on sexuality. Two percent of boys and 10% of girls had ever had at least one sexual contact with the same sex. The percentage of sexually active secondary-school students in Slovenia is high. The use of contraceptive pill is favorable, b ut the condom use needs to be further promoted.
Keywords: Adolescenca; Adolescence; Adolescent Behavior; Adolescentno vedenje; ankete; Contraception; Kontracepcija; mladostniki; Questionnaires; Sex Behavior; Sexually Transmitted Diseases; spolne bolezni; spolni odnosi; Spolno prenosljive bolezni; Spolno vedenje; srednješolci; zaščita